GE_GERICHTE C/17546/2014 vom 9. September 2016 - GE Cour de justice (2016)
RELATIONS PERSONNELLES ; CURATELLE ; PRÉVOYANCE PROFESSIONNELLE SELON LA LPP ; PARTAGE(SENS GÉNÉRAL) ; ABUS DE DROIT | CC.273; CC.308; CC.122;